Spatial Heterogeneity in Particle‐Associated, Light‐Independent Superoxide Production Within Productive Coastal Waters. Issue 10 (16th October 2020) - Sutherland, Kevin M.; Grabb, Kalina C.; Karolewski, Jennifer S.; Plummer, Sydney; Farfan, Gabriela A.; Wankel, Scott D.; Diaz, Julia M.; Lamborg, Carl H.; Hansel, Colleen M.
Abstract: In the marine environment, the reactive oxygen species (ROS) superoxide is produced through a diverse array of light‐dependent and light‐independent reactions, the latter of which is thought to be primarily controlled by microorganisms. Marine superoxide production influences organic matter remineralization, metal redox cycling, and dissolved oxygen concentrations, yet the relative contributions of different sources to total superoxide production remain poorly constrained. Here we investigate the production, steady‐state concentration, and particle‐associated nature of light‐independent superoxide in productive waters off the northeast coast of North America. We find exceptionally high levels of light‐independent superoxide in the marine water column, with concentrations ranging from 10 pM to in excess of 2, 000 pM. The highest superoxide concentrations were particle associated in surface seawater and in aphotic seawater collected meters off the seafloor. Filtration of seawater overlying the continental shelf lowered the light‐independent, steady‐state superoxide concentration by an average of 84%. We identify eukaryotic phytoplankton as the dominant particle‐associated source of superoxide to these coastal waters. We contrast these measurements with those collected at an off‐shelf station, where superoxide concentrations did not exceed 100 pM, and particles account for an average of 40% of the steady‐state superoxide concentration. This study demonstrates the primary role of particles in the production of superoxide in seawater overlying the continental shelf and highlights the importance of light‐independent, dissolved‐phase reactions in marine ROS production. Plain Language Summary: Superoxide is a reactive oxygen species (ROS) that forms in seawater as a result of light‐dependent and light‐independent reactions. This molecule is relatively short lived, and its tendency to react with nutrients including organic carbon and metals makes it an important player in many element cycles essential to life. Although the origin of light‐independent superoxide production is thought to primarily result from the extracellular production of superoxide by microorganisms, this notion is largely untested. In this study, we investigated the concentration and production rate of light‐independent superoxide in coastal waters off the northeast coast of North America. We found that light‐independent superoxide concentrations exhibited significant spatial heterogeneity (10–2, 000 pM) and that filtration of particles lowered superoxide concentrations by 84% and 40% in seawater collected on and off the continental shelf, respectively. We found that eukaryotic phytoplankton are most closely associated with light‐independent superoxide concentrations in these coastal waters. This work demonstrates that microorganisms can account for a significant fraction light‐independent superoxide in the marine environment, but dissolved‐phase superoxide production can also contribute significantly to light‐independent ROS production, particularly in deep, off‐shelf waters. Key Points: Light‐independent superoxide concentrations exhibit significant variability in coastal waters along the northeast coast of North America Particles account for most light‐independent superoxide production in coastal water, but dissolved‐phase superoxide production also occurs Chlorophyll and eukaryotes are correlated with superoxide production rate, suggesting that eukaryotic phytoplankton are important ROS producers